Bugis Language Interference with the Use of Indonesian Language in Communicating Students at SMP Negeri 1 Pammana - Sri Wahyuni; Ahmad Ghazali Samad (Universitas Sembilanbelas November Kolaka, 2019)
This research based on the processes that language learning must be carried out following the rules. The school which is a place of formal education in educating students to use Indonesian language is good and right, in the form of written and oral terms. However, in reality, the problem of Indonesian conversion is still often found in schools, at various levels starting from the higher level, which is the cause of language acquisition and mastery of more than one language (bilingual). This can be done error which is usually called interference. Interference in language is usually called